Povezanost med slogi navezanosti partnerjev in kakovostjo partnerskega odnosa - Erzetič, Robi (Psihološka obzorja (Ljubljana), 2023)
The purpose of this review was to find out how different attachment style can influence relationship quality. In our review, we included 15 researches that were conducted between years 2017 and 2021 from 4 different data bases. Leaving some exceptions on the side, our results indicates the importance of all attachment styles for relationship quality. Our results in the broadest sense suggest that securely attached individual experience more quality relationship than those who are insecurely attached. Most of the studies involved suggests negative correlation between anxious attachment, avoidant attachment style and relationship quality. Anxious and avoidant attachment are related to psychological abuse, sexual coercion and destructive communication pattern withdrawing from conflict. Anxious attachment is also related with destructive communication pattern involvment in conflict. There are also some differences in correlation between relationship quality and avoidant attachment and anxious attachment depending on gender, intelligence and socicultural factors.
Keywords: attachment behavior; attachment styles; kakovost medosebnih odnosov; literature review; navezanost; partnerski odnosi; pregled literature; relationship quality; romantic relationships; stili navezanosti